What is earning management in sharia bank lower than conventional bank? - Nurianah, Nurianah (Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
Purpose - This study is to examine the effect of sharia status on the level of earning management in Banking Companies in Indonesia.Method - This study use pooled data regression analysis and independent sample t-test to test the level of earning management between Islamic banks and non-Islamic banks. We use sample of Islamic banks and non-Islamic banks in Indonesia in the year 2009-2013.Result - We find the Islamic banks employ less earning management than non-Islamic banks. The results show that, as hypothesised, Islamic banks status has a significant negative association with earning management in regression model. This Suggest that Islamic banks have lower discressionary accrual than non-Islamic banks ans Islamic ethics palys monitoring role in reducing managerial opportunistic behaviors to manage earnings by discretionary accruals.Implication - At least the sample in this study was due to the limited number of Islamic banks and conventional banks in Indonesia. The discretionary accrual model used in this study may not be able to detect earnings management properly, so that there is a need to readjust other models related to earnings management.Originality - Earnings management has become a global issue, but for Islamic banking based on religious principles, the practice of earnings management can be minimized or eliminated. Then provide information about the high and low earnings management in banks, especially Islamic and conventional banking in Indonesia.